2017
DOI: 10.3389/fcimb.2017.00005
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism Underlying the Innate Immune Response Induction upon Viral-Dependent Replication of Host Cell mRNA: A Mistake of +sRNA Viruses' Replicases

Abstract: Viruses are lifeless particles designed for setting virus-host interactome assuring a new generation of virions for dissemination. This interactome generates a pressure on host organisms evolving mechanisms to neutralize viral infection, which places the pressure back onto virus, a process known as virus-host cell co-evolution. Positive-single stranded RNA (+sRNA) viruses are an important group of viral agents illustrating this interesting phenomenon. During replication, their genomic +sRNA is employed as temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 93 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…Most ARI resolve within one to two weeks and the host response is driven to a large extent by the innate immune system. Innate immune responses are triggered by signaling via pattern-recognition receptors (PRR) such as Toll-like receptors (TLR), double-strand RNA-activated protein kinase R (PKR) and retinoic acid-inducible gene-I (RIG-I)-like receptors that sense pathogen-associated molecular patterns (PAMPs) [6,7]. PRR funnel their signals into interactions with regulated signaling cascades, which then initiate the key antiviral interferon response as well as other common anti-viral and innate immune responses [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Most ARI resolve within one to two weeks and the host response is driven to a large extent by the innate immune system. Innate immune responses are triggered by signaling via pattern-recognition receptors (PRR) such as Toll-like receptors (TLR), double-strand RNA-activated protein kinase R (PKR) and retinoic acid-inducible gene-I (RIG-I)-like receptors that sense pathogen-associated molecular patterns (PAMPs) [6,7]. PRR funnel their signals into interactions with regulated signaling cascades, which then initiate the key antiviral interferon response as well as other common anti-viral and innate immune responses [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Double labelling of organelle and viral nonstructural proteins showed that CPV-I are derivatives of late endosomes and lysosomes, while monensin treatment results in accumulation of E1/E2 glycoproteins of SFV in the trans-Golgi network (TGN), indicating the TGN origin of CPV-II [43,44]. The replication complexes are strategically concentrated in CPV-I and replication spherules for efficient viral genome replication and to escape the cellular antiviral response [45]. These replication spherules that have access to the host cellular raw materials through an opening toward the cytoplasm were seen either inside CPV-I or transported to the plasma membrane [42,46].…”
Section: Discussionmentioning
confidence: 99%
“…Double labeling of organelle and viral nonstructural proteins showed that CPV-I are derivatives of late endosomes and lysosomes, while monensin treatment results in accumulation of E1/E2 glycoproteins of SFV in the trans-Golgi network (TGN), indicating TGN origin of CPV-II 26,27 . The replication complexes are strategically concentrated in CPV-I and replication spherule for efficient viral genome replication and to escape the cellular antiviral response 28 . These replication spherules that has access to the host cellular raw materials through an opening toward the cytoplasm were seen either inside CPV-I or transported to the plasma membrane 29 Most commonly blebs are seen during apoptosis and contains part of the cytoplasm (~2%) with or without organellar fragments for recycling by the phagocytic cells 35,36 .…”
Section: Discussionmentioning
confidence: 99%